35.1k views
2 votes
X to the one third power times x to the one third power times x to the one third power

X to the one third power times x to the one third power times x to the one third power-example-1

1 Answer

2 votes

Given:


x^{(1)/(3)}* x^{(1)/(3)}* x^{(1)/(3)}

To Determine: The simplification of the given

Solution

Given exponent rule below


a^m* a^n=a^(m+n)

Apply the exponent rule above to the question


x^{(1)/(3)}* x^{(1)/(3)}* z^{(1)/(3)}=x^{(1)/(3)+(1)/(3)+(1)/(3)}=x^{(1+1+1)/(3)}=x^{(3)/(3)}=x^1=x

Hence, the solution is x

User Rusmir
by
4.9k points